Spatial Conditions and the Climatic Comfort of the Micro-Interior - Selected Issues - Mamedov, Alirza; Kobylarczyk, Justyna (Journal of Environmental Science and Engineering Technology, 2020)
The article presents the results of research on the evaluation of the variability of selected climatic factors such as the temperature, gust and speed of wind in different locations (urban and extra-urban zones). The conducted research allowed to formulate a preliminary conclusion that the degree of openness of the micro-interior and its morphology has a direct impact on the microclimate of urban interiors. The results of the analysis led to the assumption that further research may confirm the close relationship between spatial and climatic conditions, and thus these observations may be important (while continuing the research and, consequently, confirming the conclusions) for the design practice in striving to improve the quality of the housing environment.